PEMBANGUNAN DAERAH DALAM KEMISKINAN DAN KONVERGENSI/ DIVERGENSI WILAYAH - Doddy Aditya Iskandar; Indra Andrianto (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2019)
A integrated and sustainable development is oriented towards improving people's welfare. However, disparity and poverty are still issues of development. Infrastructure and a sustainable inclusive economy are the priorities of national policies to reduce regional and socio-economic disparities by increasing connectivity between regions. The purpose of the study is to identify the conditions that are necessary and sufficient in regional development through government spending and infrastructure and economic programs on poverty as an indicator of regional disparity. This study uses a qualitative and quantitative "mix method" approach with the "Qualitative Comparative Analysis" method using case data from 20 sub-districts in Banjarnegara Regency in 2013-2017. Poor families as "outcome" variables with village fund allocation, budget and infrastructure programs, economic programs, and accessibility as casual variables. The results showed that most of the high poverty was in the northern region of Serayu River, while the southern region had higher accessibility. Within the district, based on the value of the consistency and coverage of the combination of variables, the infrastructure budget and economic program are necessary conditions and sufficient in the result of the reduction in the number of poor families. Other variables need but do not have an effect on reducing poverty. The conditions that need to be in place for the reduction of poor families in the southern region are the budget and infrastructure programs, while the northern region is the allocation of village funds and economic programs.